Acid rain - Lucas, Eileen (Chicago : Children's Press, 1991)
Discusses the causes and harmful effects of acid rain and examines possible solutions for this pollution problem.
Includes index.
Keywords: Acid rain -- Environmental aspects -- Juvenile literature; Air -- Pollution -- Juvenile literature; Acid rain; Air -- Pollution; Pollution